Biomechanical Dynamics of Cranial Sutures during Simulated Impulsive Loading - Z. Q. Zhang; J. L. Yang (Applied Bionics and Biomechanics)
Background. Cranial sutures are deformable joints between the bones of the skull, bridged by collagen fibres. They function to hold the bones of the skull together while allowing for mechanical stress transmission and deformation. Objective. The aim of this study is to investigate how cranial suture morphology, suture material property, and the arrangement of sutural collagen fibres influence the dynamic responses of the suture and surrounding bone under impulsive loads. Methods. An idealized bone-suture-bone complex was analyzed using a two-dimensional finite element model. A uniform impulsive loading was applied to the complex. Outcome variables of von Mises stress and strain energy were evaluated to characterize the sutures’ biomechanical behavior. Results. Parametric studies revealed that the suture strain energy and the patterns of Mises stress in both the suture and surrounding bone were strongly dependent on the suture morphologies. Conclusions. It was concluded that the higher order hierarchical suture morphology, lower suture elastic modulus, and the better collagen fiber orientation must benefit the stress attenuation and energy absorption.